UCP2 regulates mitochondrial fission and ventromedial nucleus control of glucose responsiveness - Toda, Chitoku (Cell, 2016)
The ventromedial nucleus of the hypothalamus (VMH) plays a critical role in regulating systemic glucose homeostasis. How neurons in this brain area adapt to the changing metabolic environment to regulate circulating glucose levels is ill-defined. Here we show that glucose load results in mitochondrial fission and reduced reactive oxygen species in VMH neurons mediated by dynamin-related peptide 1 (DRP1) under the control of uncoupling protein 2 (UCP2). Probed by genetic manipulations and chemical-genetic control of VMH neuronal circuitry, we unmasked that this mitochondrial adaptation determines the size of the pool of glucose-excited neurons in the VMH, and, that this process regulates systemic glucose homoeostasis. Thus, our data unmasked a critical cellular biological process controlled by mitochondrial dynamics in VMH regulation of systemic glucose homeostasis.